Urban Farming Prototype Design and Development with IoT System using STEMSEL and Runlinc IDE - Yaw Long Chua,; Jay Shen Gan,; Yit Yan Koh, (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2023)
Urban farming technology is getting more acceptable with the increase in population. Running urban farming with IoT becomes more important as urban farming has many constraints. This project aimed to design and develop an automated urban farming system operated with an IoT system using Science Technology Engineering Maths Social Enterprise Learning Artificial Intelligence (STEMSEL AI), and Runlinc Integrated Development Environment (IDE) to ease urban farming. The prototype consists of three major components: the structural part, the water piping system, and the IoT operating system. Idea generation was applied to develop various conceptual designs in the structural component. Concept evaluation was performed to choose the final design. The IoT operation system was designed and developed using the STEMSEL module and Runlinc IDE. A few challenges were identified throughout the design process. Overall, STEMSEL is much simpler and easier to set up than other controllers.